Effectiveness of cognitive- behavioural training on depression among mothers of mentally disabled children - P.VIJAYASAMUNDEESWARI,; PROF.DR.P.VENKATARAMAN,; DR.ANITA DAVID,; PROF.DR.O.S.RAVINDARAN, (International Journal of Pharma and Bio Sciences, 2019)
Birth of a baby is supposed to make the parents feel excited and wonderful but these feelings turn into disappointment when they come to know about the disability of their newly born. In both the parents (Mother and Father), the news of having a child with disability induces complex feelings like those of emotional shock, denial, guilt, anxiety and depression. The continuing care of children with mental retardation is often stressful for parents .Researchers have indicated that parents of children with mental retardation are generally at risk for a variety of emotional difficulties .Toassess the effectiveness of cognitive- behavioural training on depression among mothers of mentally disabled children. The conceptual framework for this study was adopted from Ernestine Wiedenbach’s “THE HELPING ART OF CLINICAL NURSING” (1964). Wiedenbach’s model focuses on the concept of implementing need based care. Sample population was including 40 mothers that were selected by cluster sampling and allocated randomly in experimental and control groups (20 parents for experimental group and 20 for control group based on the inclusion exclusion criteria. One group pretest and post test design was adopted for this study. Depression was assessed by using Beck depression scale was .8 weeks cognitive behavioural training was given to the mothers after the pre test. Each session was conducted for 60 min. The findings of the study depicted an evidence of significant difference in the pre test mean score of 25.29 and post test mean score of 14.38 with mean difference 10.91. It was highly significant at p<0.001 level. Study conclude that Cognitive behavioural training is effective in improving mental health, depression and social interaction among among mothers of mentally disabled children